THE EFFECT OF JOB SATISFACTION, ORGANIZATIONAL COMMITMENT, AND WORK ENVIRONMENT ON TURNOVER INTENTION AT PT. HASJRAT ABADI SUDIRMAN - Ephifania Sartje Louisa Bagau; Paulus Kindangen; Ferdinand J. Tumewu (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
The purpose of this study was to know the effect of job satisfaction, organizational commitment, and work environment on turnover intention at PT. Hasjrat Abadi Sudirman. This study uses a population as a sample, where the total number of respondents is 86 employees. This research was carried out using quantitative methods and data collection techniques by distributing questionnaires. The research results show that job satisfaction has a significant negative effect on turnover intention, organizational commitment has a significant negative effect on turnover intention, while the work environment has no effect on turnover intention. Simultaneously job satisfaction, organizational commitment, and work environment have an influence on employee turnover intention at PT. Hasjrat Abadi Sudirman.   Keyword: turnover intention, job satisfaction, organizational commitment, work environment